Effect of Organic Manures and Biofertilizers on the Productivity of Tomato and Bell Pepper under Mid-Hill Conditions of Himachal Pradesh - A. S. Kashyap; Ashok K. Thakur; Nitika Thakur (International Journal of Economic Plants)
A field study on the effect of organic manures and biofertilizers was conducted on the farmer field during the years (2009-10) and (2010-11). Heem Sohna, Rakshita, Naveen+2000 and Sun Seed 7711 varieties of tomato and K. Sel, California Wonder, Indra and Dollar varieties of capsicum were taken for the present studies. Farm Yard Manure (FYM) at the rate of 30 tones per hectare and vermicompost (VC) at the rate of 6 tones per hectares treated with Tichoderma viridi at the rate of 500 gm/2 tones of manures were made at the time of field preparation and during different stages of growth. In conventional treatment recommended doses of fertilizers and FYM were applied. In chemical treatments only recommended fertilizer dosages were used. The spacing adopted in tomato was 60×30 cm and 45×30 cm in capsicum. The highest yield of 134.4 tones/hectare in case of tomato variety Rakshita and 65.0 tones/ hectare in capsicum variety Dollar were recorded in conventional system whereas the corresponding figures were slightly less in organic system of cultivation. However, the yields in both the crops were drastically reduced under chemical cultivation. The fruit quality attributes were marginally higher in organic system of cultivation and the crop longevity was also noted to be prolonged to the considerable extent.